2002
DOI: 10.1590/s0103-64402002000200002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of tissue response to polyglecaprone 25, polyglactin 910 and polytetrafluorethylene suture materials in rats

Abstract: The authors evaluated the biocompatibility of three suture materials, polyglecaprone 25, polyglactin 910 and polytetrafluorethylene, implanted into subcutaneous tissue in the dorsal region of 20 Wistar albinus rats. After periods of 2, 7, 14 and 21 days, the rats were sacrificed and the specimens were processed for routine histotechnical analysis and stained with hematoxylin and eosin. The rate of fibrosis, angioblastic and fibroblastic proliferation, and also the intensity of inflammation were observed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Other rat studies have evaluated PDS II®, MONOCRYL®, VICRYL®, Chromic Gut® and e-PTFE®. Despite acceptance from the animals, VICRYL® suture showed the highest level of inflammation on histological evaluation [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Other rat studies have evaluated PDS II®, MONOCRYL®, VICRYL®, Chromic Gut® and e-PTFE®. Despite acceptance from the animals, VICRYL® suture showed the highest level of inflammation on histological evaluation [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…PG is a synthetic, absorbable, braided suture consisting of 90% glycolide and 10% L-lactide [8]. Poliglecaprone 25 monofilament suture material, a copolymer of glycolide and e-caprolactone, is absorbed by hydrolysis in a period of 91 to 119 days, has excellent strength, minimal memory, and a great deal of malleability [9]. Studies have examined the tensile strength and resorption rates of different suture materials, and it has been found that the tensile strength of sutures decreased over time and was dependent on the rate of resorption [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining the tissue reactions of polyglactin 910, poliglecaprone 25 and polytetrafluoroethylene (PTFE) suture materials in Wistar albino rats, fibrosis, angioblastic and fibroblastic proliferations, and inflammation intensities were evaluated histologically on the 2nd, 7th, 14th and 21st days by optical microscopy. According to the results of the study, the frequency of tissue reaction was found to be in the following order: polilecaprone 25, polyglactin 910 and polytetrafluoroethylene [29]. When the studies were evaluated in general, it was observed that monofilament sutures caused less tissue reaction and inflammation than multifilament sutures.…”
Section: Discussionmentioning
confidence: 93%